Key pedagogical and technological factors for effective blended learning design - Bidarra, José (2017)
This is a report by the expert pools of the EMPOWER programme established by EADTU to cover the latest trends and developments in new modes of teaching. New modes of teaching and learning create new opportunities for enhancing the quality of the learning experience in on campus programmes, reaching out to new target groups off campus and offering freely accessible courses nationally or worldwide through the internet. They enhance the quality, visibility and reputation of the institution.